2004
DOI: 10.1002/app.20528
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varied imidization conditions on rubbed polyimide film surface morphology

Abstract: ABSTRACT:The thermal histories of polyimide films were varied to study the effect of the extent of imidization on the response of films to rubbing. Films rubbed prior to imidization formed tears that extended to the substrate; tears in these films formed at smaller film thicknesses than in films imidized prior to rubbing. Aligned nanoscopic islands were also seen. The alignment of these islands disappeared upon imidization. Films imidized at a low temperature showed less alignment of islands than conventionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, a low imidization temperature using a base catalyst such as 1,4-diazobicyclo[2.2.2]octane (DABCO) and 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) to prepare composite films effectively improved mechanical properties, which can reduce the elimination of functional groups on GNS at high temperatures. 17,18 We also demonstrated that the water vapor permeability of composite films decreased significantly by 74% compared to that of pure PI.…”
Section: ■ Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, a low imidization temperature using a base catalyst such as 1,4-diazobicyclo[2.2.2]octane (DABCO) and 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) to prepare composite films effectively improved mechanical properties, which can reduce the elimination of functional groups on GNS at high temperatures. 17,18 We also demonstrated that the water vapor permeability of composite films decreased significantly by 74% compared to that of pure PI.…”
Section: ■ Introductionmentioning
confidence: 75%
“…APGNS can not only improve homogeneous dispersion in a polar solvent but also enhance mechanical properties while maintaining high electrical conductivity, owing to covalent bonding between the PI matrix and the GNS. Moreover, a low imidization temperature using a base catalyst such as 1,4-diazobicyclo[2.2.2]octane (DABCO) and 1,8-diaza-bicyclo[5.4.0]undec-7-ene (DBU) to prepare composite films effectively improved mechanical properties, which can reduce the elimination of functional groups on GNS at high temperatures. , We also demonstrated that the water vapor permeability of composite films decreased significantly by 74% compared to that of pure PI.…”
Section: Introductionmentioning
confidence: 76%
“…It can be clearly seen that the surface became rougher with increasing imidization temperature, creating a distinctive surface structure [10]. This indicates that the films of PAA and fully cured PI have comparable roughness and thickness uniformity; i.e.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 88%